Sustainable Business Strategy: An Analysis Of An Indonesian Manufacturing Company - Wulandari, Suaida Ayu; Amir, Muhammad Taufiq (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
The increasing issue of climate change has led to growing interest in sustainability especially for business. Consumers and people in general, have become more aware and concerned about their environmental footprint, which put pressure for businesses to develop and implement a comprehensive climate strategy which are included in the company’s sustainable strategy. The study on sustainability and sustainable business strategy has been increasing. However, in Indonesia this topic is relatively new and unexplored, thus it needs further discussion. This study examines the sustainable business strategy in a Fast-Moving Consumers Goods manufacturing company in Indonesia. The questions asked in this research include the company’s stage on sustainability effort and whether the company’s sustainable strategy has an impact in terms of the triple bottom line aspects of sustainability. The sustainability dimensions in the form of triple bottom line is explained as a basis for analysis. The study uses qualitative method using document analysis and interview to examine the stage of sustainable business strategy. The results suggested that the company’s sustainability effort is considered as holistic approach. It also suggests that the company’s effort in sustainability contribute to the economic well-being of the company and the stakeholders as well as social and environmental contribution. This research is expected to give a glimpse of the Indonesian manufacturing company’s effort on sustainable business practice which can be used as an inspiration for other companies in the same industries or by other industries to follow and implement a sustainable business strategy of their own.